EXPLORING CHINESE EFL TEACHERS’ KNOWLEDGE IN CONTENT, PEDAGOGY, AND TECHNOLOGY INTEGRATION (TPACK) - Shi, Leimin; Jiang, Lili (LLT Journal: A Journal on Language and Language Teaching, 2025)
This study investigates the Technological Pedagogical Content Knowledge (TPACK) of Chinese English as a foreign language (EFL) teachers from both student and teacher perspectives. As technology increasingly permeates education, understanding teachers’ TPACK factors, encompassing the interplay of the primary knowledge of content (CK), pedagogy (PK), and technology (TK), is crucial. Teachers’ perceptions of TPACK factors significantly impact the success of technology-integrated teaching. Equally important are students’ beliefs, which directly influence motivation and satisfaction. Aligning both perspectives helps educators better address students’ needs and expectations. A survey involving 694 university EFL students was compared with survey responses from 64 teachers, supplemented by interviews with nine teachers. Both cohorts acknowledged the importance of technology in facilitating CK delivery. PK and CK were deemed the most important, while TK was ranked lowest among the seven TPACK factors. However, teachers prioritised pedagogical content knowledge, whereas students emphasised technology integration. Moreover, teachers showed greater variability in their perceptions across most knowledge factors. These perceptions reflected the influence of demographic backgrounds and contextual factors. These findings underscore the significance of enhancing teachers’ technology-integrated knowledge and implementation strategies to meet student expectations. The implications are significant for educators and professional development providers in designing training programs and support systems.